Aspergillus fumigatus Spores Are Not Able to Penetrate Silicone Breast Implant Shells - Horch, Raymund E.; Krappmann, Sven; Duemig, Michaela; Schmitz, Marweh; Kengelbach-Weigand, Annika; Schubert, Dirk W.; Kremser, Thomas; Bogdan, Christian; Ludolph, Ingo (Annals of Plastic Surgery, 2019)
Bacterial contamination is hypothesized to be one reason for the development of capsular contracture after alloplastic breast reconstruction using silicone breast implants. The role of fungal colonization or infection in this context as well as the question if microorganisms can penetrate the shell of silicone breast implants remains an unresolved question to date. Therefore, the aim of this study was to assess whether fungal spores are able to penetrate the shell of silicone implants. In an experimental in vitro setup with different arrangements of growth compartments, silicone chambers were placed in culture dishes filled with Aspergillus minimal medium or liquid culture medium. Inoculation was performed with conidia of Aspergillus fumigatus and incubated for seven days. On a daily basis, plates were inspected for conidial germination and hyphal growth. In none of the different experimental settings nutrients or hyphae of Aspergillus fumigatus were able to penetrate the silicone material.ConclusionsFungal spores and hyphae do not permeate through an intact silicone shell used in breast implants; thus, the silicone material serves as an impenetrable barrie
Keywords: Aspergillus fumigatus; penetration; silicone implants; breast

CRISPR-Cas9, the new kid on the block of fungal molecular biology - Krappmann, Sven (Medical Mycology, 2017)
Research on fungal pathogens with the aim to identify virulence determinants strictly relies on the generation of defined, recombinant strains, a task that is executed by means of a sophisticated molecular biology toolbox. Recent developments in fungal genome engineering have opened a new frontier by implementing the CRISPR-Cas9 technology, based on expression of the Cas9 endonuclease that is loaded by a single guiding RNA (sgRNA) molecule to target a defined site in the recipient genome. This novel approach has been adapted successfully to engineer fungal genomes, among them the one of the human-pathogenic mould Aspergillus fumigatus Implementation of the required components was achieved by various means that differ with respect to expression of the Cas9 enzyme and sgRNA delivery. Validation of CRISPR-Cas9-mediated mutagenesis could be executed by targeting selected candidate genes of A. fumigatus to provide a promising perspective for screening and multiplexing approaches to scrutinize the virulome of this opportunistic fungal pathogen in a comprehensive manner, such as by analyzing genetic polymorphisms or the function of gene families.
EVALuna2:7747

Determinants of the interaction of Aspergillus fumigatus and eosinophils in the context of allergic bronchopulmonary aspergillosis - Adam, Jasmin; Schrüfer, Sebastian; Westermann, Stefanie; Vöhringer, David; Krappmann, Sven (MYCOSES, 2022)
CRIS-Team WoS Importer:2022-09-23

Direct Visualization of Fungal Burden in Filamentous Fungus-Infected Silkworms - Yu, Yidong; Wolf, Ann-Katrin; Thusek, Sina; Heinekamp, Thorsten; Bromley, Michael; Krappmann, Sven; Terpitz, Ulrich; Voigt, Kerstin; Brakhage, Axel A.; Beilhack, Andreas (Journal of Fungi, 2021)
Invasive fungal infections (IFIs) are difficult to diagnose and to treat and, despite several available antifungal drugs, cause high mortality rates. In the past decades, the incidence of IFIs has continuously increased. More recently, SARS-CoV-2-associated lethal IFIs have been reported worldwide in critically ill patients. Combating IFIs requires a more profound understanding of fungal pathogenicity to facilitate the development of novel antifungal strategies. Animal models are indispensable for studying fungal infections and to develop new antifungals. However, using mammalian animal models faces various hurdles including ethical issues and high costs, which makes large-scale infection experiments extremely challenging. To overcome these limitations, we optimized an invertebrate model and introduced a simple calcofluor white (CW) staining protocol to macroscopically and microscopically monitor disease progression in silkworms (Bombyx mori) infected with the human pathogenic filamentous fungi Aspergillus fumigatus and Lichtheimia corymbifera. This advanced silkworm A. fumigatus infection model could validate knockout mutants with either attenuated, strongly attenuated or unchanged virulence. Finally, CW staining allowed us to efficiently visualize antifungal treatment outcomes in infected silkworms. Conclusively, we here present a powerful animal model combined with a straightforward staining protocol to expedite large-scale in vivo research of fungal pathogenicity and to investigate novel antifungal candidates.
CRIS-Team WoS Importer:2021-03-12

Editorial: Sulphur Metabolism of Fungi - Implications for Virulence and Opportunities for Therapy - Amich, Jorge; Krappmann, Sven; Bachhawat, Anand Kumar (Frontiers in Microbiology, 2020)
CRIS-Team Scopus Importer:2020-11-06
Keywords: fungal primary metabolism; implications for virulence; opportunities for therapy; pathogenic fungi; sulfur metabolism of fungi

Exogenous TNFR2 activation protects from acute GvHD via host T reg cell expansion - Chopra, Martin; Biehl, Marlene; Steinfatt, Tim; Brandl, Andreas; Kums, Juliane; Amich, Jorge; Vaeth, Martin; Kuen, Janina; Holtappels, Rafaela; Podlech, Juergen; Mottok, Anja; Kraus, Sabrina; et al. (Journal of Experimental Medicine, 2016)
Donor CD4(+)Foxp3(+) regulatory T cells (T reg cells) suppress graft-versus-host disease (GvHD) after allogeneic hematopoietic stem cell transplantation (HCT [allo-HCT]). Current clinical study protocols rely on the ex vivo expansion of donor T reg cells and their infusion in high numbers. In this study, we present a novel strategy for inhibiting GvHD that is based on the in vivo expansion of recipient T reg cells before allo-HCT, exploiting the crucial role of tumor necrosis factor receptor 2 (TNFR2) in T reg cell biology. Expanding radiation-resistant host T reg cells in recipient mice using a mouse TNFR2-selective agonist before allo-HCT significantly prolonged survival and reduced GvHD severity in a TNFR2- and T reg cell-dependent manner. The beneficial effects of transplanted T cells against leukemia cells and infectious pathogens remained unaffected. A corresponding human TNFR2-specific agonist expanded human T reg cells in vitro. These observations indicate the potential of our strategy to protect allo-HCT patients from acute GvHD by expanding T reg cells via selective TNFR2 activation in vivo.
EVALuna2:7721

Exploration of Sulfur Assimilation of Aspergillus fumigatus Reveals Biosynthesis of Sulfur-Containing Amino Acids as a Virulence Determinant - Amich, Jorge; Duemig, Michaela; O'Keeffe, Grainne; Binder, Jasmin; Doyle, Sean; Beilhack, Andreas; Krappmann, Sven (Infection and Immunity, 2016)
Fungal infections are of major relevance due to the increased numbers of immunocompromised patients, frequently delayed diagnosis, and limited therapeutics. To date, the growth and nutritional requirements of fungi during infection, which are relevant for invasion of the host, are poorly understood. This is particularly true for invasive pulmonary aspergillosis, as so far, sources of (macro)elements that are exploited during infection have been identified to only a limited extent. Here, we have investigated sulfur (S) utilization by the human-pathogenic mold Aspergillus fumigatus during invasive growth. Our data reveal that inorganic S compounds or taurine is unlikely to serve as an S source during invasive pulmonary aspergillosis since a sulfate transporter mutant strain and a sulfite reductase mutant strain are fully virulent. In contrast, the S-containing amino acid cysteine is limiting for fungal growth, as proven by the reduced virulence of a cysteine auxotroph. Moreover, phenotypic characterization of this strain further revealed the robustness of the subordinate glutathione redox system. Interestingly, we demonstrate that methionine synthase is essential for A. fumigatus virulence, defining the biosynthetic route of this proteinogenic amino acid as a potential antifungal target. In conclusion, we provide novel insights into the nutritional requirements ofA. fumigatus during pathogenesis, a prerequisite to understanding and fighting infection.
EVALuna2:7707

Genetic surgery in fungi: employing site-specific recombinases for genome manipulation - Krappmann, Sven (Applied Microbiology and Biotechnology, 2014)
Site-specific recombination mediates the rearrangement of nucleic acids by the virtue of an recombinase acting on specific recognition sequences. Recombining activities belong either to the tyrosine- or serine-type group, based on the presence of specific residues in the catalytic centre, which can be further subdivided into families due to additional criteria. The most prominent systems are the ? phage integrase acting on att sites; the Cre recombinase from bacteriophage P1 with its loxP attachment sites; the FLP/FTR system of fungal origin, where it is required for 2-?m plasmid replication/amplification in yeast; and the prokaryotic ?-recombinase that recombines six sites specifically in cis. Each of these has been exploited in fungal hosts of biotechnological, medical or general relevance, mainly for cloning projects, approaches of gene targeting, genome modification or screening purposes. With their precise and defined mode of action are site-specific recombination systems eminently suited for genetic tasks in fungi, like they are executed in functional studies at high throughput or modern approaches of synthetic biology.
EVALuna2:7574

How to invade a susceptible host: cellular aspects of aspergillosis - Krappmann, Sven (Current Opinion in Microbiology, 2016)
Diseases caused by Aspergillus spp. and in particular A. fumigatus are manifold and affect individuals suffering from immune dysfunctions, among them immunocompromised ones. The determinants of whether the encounter of a susceptible host with infectious propagules of this filamentous saprobe results in infection have been characterized to a limited extent. Several cellular characteristics of A. fumigatus that have evolved in its natural environment contribute to its virulence, among them general traits as well as particular ones that affect interaction with the mammalian host. Among the latter, conidial constituents, cell wall components, secreted proteins as well as extrolites shape the tight interaction of A. fumigatus with the host milieu and also contribute to evasion from immune surveillance.
EVALuna2:7748

Human dendritic cell subsets display distinct interactions with the pathogenic mould Aspergillus fumigatus - Lother, Jasmin; Breitschopf, Tanja; Krappmann, Sven; Morton, C. Oliver; Bouzani, Maria; Kurzai, Oliver; Gunzer, Matthias; Hasenberg, Mike; Einsele, Hermann; Loeffler, Juergen (International Journal of Medical Microbiology, 2014)
The mould Aspergillus fumigatus is primarily an opportunistic pathogen of immunocompromised patients. Once fungal spores have been inhaled they encounter cells of the innate immune system, which include dendritic cells (DCs). DCs are the key antigen-presenting cells of the immune system and distinct subtypes, which differ in terms of origin, morphology and function. This study has systematically compared the interactions between A. fumigatus and myeloid DCs (mDCs), plasmacytoid DCs (pDCs) and monocyte-derived DCs (moDCs). Analyses were performed by time-lapse video microscopy, scanning electron microscopy, plating assays, flow cytometry, 25-plex ELISA and transwell assays. The three subsets of DCs displayed distinct responses to the fungus with mDCs and moDCs showing the greatest similarities. mDCs and moDCs both produced rough convolutions and occasionally phagocytic cups upon exposure to A. fumigatus whereas pDCs maintained a smooth appearance. Both mDCs and moDCs phagocytosed conidia and germ tubes, while pDCs did not phagocytose any fungi. Analysis of cytokine release and maturation markers revealed specific differences in pro- and anti-inflammatory patterns between the different DC subsets. These distinct characteristics between the DC subsets highlight their differences and suggest specific roles of moDCs, mDCs and pDCs during their interaction with A. fumigatus in vivo.
EVALuna2:7661

Identification of Aspergillus fumigatus Surface Components That Mediate Interaction of Conidia and Hyphae With Human Platelets - Rambach, Guenter; Blum, Gerhard; Latge, Jean-Paul; Fontaine, Thierry; Heinekamp, Thorsten; Hagleitner, Magdalena; Jeckstroem, Hanna; Weigel, Guenter; Wuertinger, Philipp; Pfaller, Kristian; Krappmann, Sven; Loeffler, Juergen; et al. (Journal of Infectious Diseases, 2015)
Platelets were recently identified as a part of innate immunity. They are activated by contact with Aspergillus fumigatus; putative consequences include antifungal defense but also thrombosis, excessive inflammation, and thrombocytopenia. We aimed to identify those fungal surface structures that mediate interaction with platelets.Human platelets were incubated with Aspergillus conidia and hyphae, isolated wall components, or fungal surface mutants. Interaction was visualized microscopically; activation was quantified by flow cytometry of specific markers.The capacity of A. fumigatus conidia to activate platelets is at least partly due to melanin, because this effect can be mimicked with "melanin ghosts"; a mutant lacking melanin showed reduced platelet stimulating potency. In contrast, conidial hydrophobin masks relevant structures, because an A. fumigatus mutant lacking the hydrophobin protein induced stronger platelet activation than wild-type conidia. A. fumigatus hyphae also contain surface structures that interact with platelets. Wall proteins, galactomannan, chitin, and ?-glucan are not the relevant hyphal components; instead, the recently identified fungal polysaccharide galactosaminogalactan potently triggered platelet activation.Conidial melanin and hydrophobin as well as hyphal galactosaminogalactan represent important pathogenicity factors that modulate platelet activity and thus might influence immune responses, inflammation, and thrombosis in infected patients.
EVALuna2:7693

ImmunoPET/MR imaging allows specific detection of Aspergillus fumigatus lung infection in vivo - Rolle, Anna-Maria; Hasenberg, Mike; Thornton, Christopher R.; Solouk-Saran, Djamschid; Maenn, Linda; Weski, Juliane; Maurer, Andreas; Fischer, Eliane; Spycher, Philipp R.; Schibli, Roger; Boschetti, Frederic; Stegemann-Koniszewski, Sabine; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Invasive pulmonary aspergillosis (IPA) is a life-threatening lung disease caused by the fungus Aspergillus fumigatus, and is a leading cause of invasive fungal infection-related mortality and morbidity in patients with hematological malignancies and bone marrow transplants. We developed and tested a novel probe for noninvasive detection of A. fumigatus lung infection based on antibody-guided positron emission tomography and magnetic resonance (immunoPET/MR) imaging. Administration of a [(64)Cu]DOTA-labeled A. fumigatus-specific monoclonal antibody (mAb), JF5, to neutrophil-depleted A. fumigatus-infected mice allowed specific localization of lung infection when combined with PET. Optical imaging with a fluorochrome-labeled version of the mAb showed colocalization with invasive hyphae. The mAb-based newly developed PET tracer [(64)Cu]DOTA-JF5 distinguished IPA from bacterial lung infections and, in contrast to [(18)F]FDG-PET, discriminated IPA from a general increase in metabolic activity associated with lung inflammation. To our knowledge, this is the first time that antibody-guided in vivo imaging has been used for noninvasive diagnosis of a fungal lung disease (IPA) of humans, an approach with enormous potential for diagnosis of infectious diseases and with potential for clinical translation.
EVALuna2:7708

Impairing fluoride export of Aspergillus fumigatus mitigates its voriconazole resistance - Binder, Jasmin; Held, Jürgen; Krappmann, Sven (International Journal of Antimicrobial Agents, 2019)
Fungi have evolved specific export activities to balance intracellular levels of the toxic ion fluoride, while the first-line antimycotic voriconazole contains fluorine. This study aimed to explore whether impaired fluoride export might result in altered susceptibilities of the human pathogenic mould Aspergillus fumigatus towards this antifungal compound. Functional characterization of the putative fluoride exporter in A. fumigatus was performed in the context of azole resistance by generating deletion strains that were assessed for their resistance against fluoride and voriconazole. The FexA fluoride exporter of A. fumigatus appears to be expressed constitutively, and targeting its encoding gene results in significantly increased sensitivity towards this halide. Impaired fluoride export correlates with increased susceptibility of an azole-resistant fexAΔ strain. These results demonstrate that the fexA-encoded gene product is the major fluoride export activity of A. fumigatus, and that voriconazole serves as a source of fluoride. However, these data do not support the application of voriconazole based on fluoride toxicity.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Aspergillosis; Azole resistance; FEX

Induction of Aspergillus fumigatus zinc cluster transcription factor OdrA/Mdu2 provides combined cellular responses for oxidative stress protection and multiple antifungal drug resistance - Sasse, Christoph; Bastakis, Emmanouil; Bakti, Fruzsina; Höfer, Annalena M.; Zangl, Isabella; Schüller, Christoph; Köhler, Anna M.; Gerke, Jennifer; Krappmann, Sven; Finkernagel, Florian; Harting, Rebekka; Strauss, Joseph; et al. (mBio, 2023)
Zinc cluster transcription factors (Zcfs) encoding zcf genes are exclusive for fungi and required for multiple cellular processes including metabolism and development. Genome-wide screening of 228 zinc cluster transcription factor encoding genes by overexpression in Aspergillus fumigatus revealed 11 genes which provided increased tolerance to the broadly applied azole voriconazole or to the polyene amphotericin B or to both. These include four oxidative stress and drug resistance genes (odrA-D) genes encoding factors, which provide broad cellular stress protection. Thereby, the corresponding fungal OdrA/Mdu2- and AtrR/OdrD-dependent genetic networks are interconnected. OdrA/Mdu2 activates atrR/odrD transcription by direct binding to the promoter, whereas AtrR/OdrD functions as repressor of odrA/mdu2 expression. odrA/ mdu2 overexpression provides combined resistance to amphotericin B, voriconazole, itraconazole, and reactive oxygen species generated by menadione. OdrA/Mdu2-mediated itraconazole resistance is evoked by direct regulation of the transporter encoding gene mdr1. Oxidative stress-inducing substances like amphotericin B and menadione promote OdrA/Mdu2 accumulation in the nucleus to regulate stress response genes like mdr1 and the putative glutathione-S-transferase encoding gene gstD. The expression levels and external stress conditions fostering nuclear accumulation of OdrA/Mdu2 determine the regulation of the target genes. Hence, OdrA/Mdu2 provides a combined adaptation strategy for survival in nature or within a potential host, where this fungus represents the most common agent for human mold pneumonia worldwide. The OdrA/ Mdu2 controlled genetic network highlights the tight connection between oxidative stress response and antifungal drug adaption to secure A. fumigatus survival in various hostile environments. IMPORTANCE An overexpression screen of 228 zinc cluster transcription factor encoding genes of A. fumigatus revealed 11 genes conferring increased tolerance to antifungal drugs. Out of these, four oxidative stress and drug tolerance transcription factor encoding odr genes increased tolerance to oxidative stress and antifungal drugs when overexpressed. This supports a correlation between oxidative stress response and antifungal drug tolerance in A. fumigatus. OdrA/Mdu2 is required for the cross-tolerance between azoles, polyenes, and oxidative stress and activates genes for detoxification. Under oxidative stress conditions or when overexpressed, OdrA/Mdu2 accumulates in the nucleus and activates detoxifying genes by direct binding at their promoters, as we describe with the mdr1 gene encoding an itraconazole specific efflux pump. Finally, this work gives new insights about drug and stress resistance in the opportunistic pathogenic fungus A. fumigatus.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Aspergillus fumigatus; atrR; drug tolerance; mdr1; OdrA/Mdu2; oxidative stress; zinc cluster transcription factors

Influence of Platelet-rich Plasma on the immune response of human monocyte-derived dendritic cells and macrophages stimulated with Aspergillus fumigatus - Czakai, Kristin; Dittrich, Marcus; Kaltdorf, Martin; Mueller, Tobias; Krappmann, Sven; Schedler, Anette; Bonin, Michael; Duehring, Sybille; Schuster, Stefan; Speth, Cornelia; Rambach, Guenter; Einsele, Hermann; et al. (International Journal of Medical Microbiology, 2017)
Dendritic cells (DCs) and macrophages (M?) are critical for protection against pathogenic fungi including Aspergillus fumigatus. To analyze the role of platelets in the innate immune response, human DCs and M?s were challenged with A. fumigatus in presence or absence of human platelet rich plasma (PRP). Gene expression analyses and functional investigations were performed. A systems biological approach was used for initial modelling of the DC - A. fumigatus interaction. DCs in a quiescent state together with different corresponding activation states were validated using gene expression data from DCs and M? stimulated with A. fumigatus. To characterize the influence of platelets on the immune response of DCs and M? to A. fumigatus, we experimentally quantified their cytokine secretion, phagocytic capacity, maturation, and metabolic activity with or without platelets. PRP in combination with A. fumigatus treatment resulted in the highest expression of the maturation markers CD80, CD83 and CD86 in DCs. Furthermore, PRP enhanced the capacity of macrophages and DCs to phagocytose A. fumigatus conidia. In parallel, PRP in combination with the innate immune cells significantly reduced the metabolic activity of the fungus. Interestingly, A. fumigatus and PRP stimulated M? showed a significantly reduced gene expression and secretion of IL6 while PRP only reduced the IL-6 secretion of A. fumigatus stimulated DCs. The in silico systems biological model correlated well with these experimental data. Different modules centrally involved in DC function became clearly apparent, including DC maturation, cytokine response and apoptosis pathways. Taken together, the ability of PRP to suppress IL-6 release of human DCs might prevent local excessive inflammatory hemorrhage, tissue infarction and necrosis in the human lung.
EVALuna2:7746

Lightning up the worm: How to probe fungal virulence in an alternative mini-host by bioluminescence - Krappmann, Sven (Virulence, 2015)
EVALuna2:7689

Magnetic Removal of Candida albicans Using Salivary Peptide-Functionalized SPIONs - Friedrich, Bernhard; Tietze, Rainer; Dümig, Michaela; Sover, Alexandru; Boca, Marius Andrei; Schreiber, Eveline; Band, Julia; Janko, Christina; Krappmann, Sven; Alexiou, Christoph; Lyer, Stefan (International Journal of Nanomedicine, 2023)
Purpose: Magnetic separation of microbes can be an effective tool for pathogen identification and diagnostic applications to reduce the time needed for sample preparation. After peptide functionalization of superparamagnetic iron oxide nanoparticles (SPIONs) with an appropriate interface, they can be used for the separation of sepsis-associated yeasts like Candida albicans. Due to their magnetic properties, the magnetic extraction of the particles in the presence of an external magnetic field ensures the accumulation of the targeted yeast. Materials and Methods: In this study, we used SPIONs coated with 3-aminopropyltriethoxysilane (APTES) and functionalized with a peptide originating from GP340 (SPION-APTES-Pep). For the first time, we investigate whether this system is suitable for the separation and enrichment of Candida albicans, we investigated its physicochemical properties and by thermogravimetric analysis we determined the amount of peptide on the SPIONs. Further, the toxicological profile was evaluated by recording cell cycle and DNA degradation. The separation efficiency was investigated using Candida albicans in different experimental settings, and regrowth experiments were carried out to show the use of SPION-APTES-Pep as a sample preparation method for the identification of fungal infections. Conclusion: SPION-APTES-Pep can magnetically remove more than 80% of the microorganism and with a high selective host-pathogen distinction Candida albicans from water-based media and about 55% in blood after 8 minutes processing without compromising effects on the cell cycle of human blood cells. Moreover, the separated fungal cells could be regrown without any restrictions.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Candida albicans; fungal sepsis; GP340; microbiological identification; SPIONs

Mating-type factor-specific regulation of the fumagillin/pseurotin secondary metabolite supercluster in Aspergillus fumigatus - Yu, Yidong; Blachowicz, Adriana; Will, Christine; Szewczyk, Edyta; Glenn, Steven; Gensberger-Reigl, Sabrina; Nowrousian, Minou; Wang, Clay C. C.; Krappmann, Sven (Molecular Microbiology, 2018)
In the human pathogenic mold Aspergillus fumigatus, sexual identity is determined by the mating-type idiomorphs MAT1-1 and MAT1-2 residing at the MAT locus. Upon crossing of compatible partners, a heterothallic mating is executed to eventually form cleistothecia that contain recombinant ascospores. Given that the MAT1 gene products are DNA binding master regulators that govern this complex developmental process, we monitored the MAT1-driven transcriptomes of A. fumigatus by conditional overexpression of either MAT1 gene followed by RNA-seq analyses. Numerous genes related to the process of mating were found to be under transcriptional control, such as pheromone production and recognition. Substantial differences between the MAT1-1- and MAT1-2-driven transcriptomes could be detected by functional categorization of differentially expressed genes. Moreover, a significant and distinct impact on expression of genetic clusters of secondary metabolism became apparent, which could be verified on the product level. Unexpectedly, specific cross-regulation of the fumagillin/pseurotin supercluster was evident, thereby uncoupling its co-regulatory characteristic. These insights imply a tight interconnection of sexual development accompanied by ascosporogenesis with secondary metabolite production of a pathogenic fungus and impose evolutionary constraints that link these two fundamental aspects of the fungal lifestyle.
EVALuna2:36418

Murine eosinophil development and allergic lung eosinophilia are largely dependent on the signaling adaptor GRB2 - Willebrand, Ralf; Dietschmann, Axel; Nitschke, Lars; Krappmann, Sven; Vöhringer, David (European Journal of Immunology, 2018)
Eosinophils are innate effector cells associated with allergic inflammation. Their development and survival is largely dependent on IL-5 and the common beta chain (βc ) of the IL-5 receptor that serves as docking site for several proteins that mediate down-stream signaling cascades including JAK/STAT, PI3 kinase, NFκB, and RAS-MAP kinase pathways. The relative contribution of these signaling pathways for eosinophil development and homeostasis in vivo are poorly understood. Here, we investigated the role of GRB2, an adaptor protein that binds to βc and other proteins and elicits the RAS-MAP kinase pathway. By using GRB2 inhibitors and inducible deletion of the Grb2 gene in mouse eosinophils we demonstrate that GRB2 plays a critical role for development of eosinophils from bone marrow precursors. Furthermore, Aspergillus fumigatus-induced allergic lung eosinophilia was significantly reduced in mice with induced genetic deletion of Grb2. Our results indicate that GRB2 is important for eosinophil development in steady-state conditions and during allergic inflammation. Based on these findings pharmacologic GRB2 inhibitors may have the potential to dampen tissue eosinophilia in various eosinophil-associated diseases.
EVALuna2:36387

On the lineage of Aspergillus fumigatus isolates in common laboratory use - Bertuzzi, Margherita; van Rhijn, Norman; Krappmann, Sven; Bowyer, Paul; Bromley, Michael J.; Bignell, Elaine M. (Medical Mycology, 2021)
The origin of isolates routinely used by the community of Aspergillus fumigatus researchers is periodically a matter of intense discussion at our centre, as the construction of recombinant isolates have sometimes followed convoluted routes, the documentation describing their lineages is fragmented, and the nomenclature is confusing. As an aide memoir, not least for our own benefit, we submit the following account and tabulated list of strains (Table 1) in an effort to collate all of the relevant information in a single, easily accessible document. To maximise the accuracy of this record we have consulted widely amongst the community of Medical Mycologists using these strains. All the strains described are currently available from one of these organisations, namely the Fungal Genetics Stock Centre (FGSC), FungiDB, Ensembl Fungi and The National Collection of Pathogenic Fungi (NCPF) at Public Health England. Display items from this manuscript are also featured on FungiDB. LAY ABSTRACT: We present a concise overview on the definition, origin and unique genetic makeup of the Aspergillus fumigatus isolates routinely in use by the fungal research community, to aid researchers to describe past and new strains and the experimental differences observed more accurately.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Aspergillus fumigatus; isolate; lineage; strain

Pathogenic fungi regulate immunity by inducing neutrophilic myeloid-derived suppressor cells - Rieber, Nikolaus; Singh, Anurag; Oez, Hasan; Carevic, Melanie; Bouzani, Maria; Amich, Jorge; Ost, Michael; Ye, Zhiyong; Ballbach, Marlene; Schaefer, Iris; Mezger, Markus; Klimosch, Sascha N.; et al. (Cell Host & Microbe, 2015)
Despite continuous contact with fungi, immunocompetent individuals rarely develop pro-inflammatory antifungal immune responses. The underlying tolerogenic mechanisms are incompletely understood. Using both mouse models and human patients, we show that infection with the human pathogenic fungi Aspergillus fumigatus and Candida albicans induces a distinct subset of neutrophilic myeloid-derived suppressor cells (MDSCs), which functionally suppress T and NK cell responses. Mechanistically, pathogenic fungi induce neutrophilic MDSCs through the pattern recognition receptor Dectin-1 and its downstream adaptor protein CARD9. Fungal MDSC induction is further dependent on pathways downstream of Dectin-1 signaling, notably reactive oxygen species (ROS) generation as well as caspase-8 activity and interleukin-1 (IL-1) production. Additionally, exogenous IL-1? induces MDSCs to comparable levels observed during C. albicans infection. Adoptive transfer and survival experiments show that MDSCs are protective during invasive C. albicans infection, but not A. fumigatus infection. These studies define an innate immune mechanism by which pathogenic fungi regulate host defense.
EVALuna2:7690

Phosphatidylinositol 3-Kinase (PI3K) Orchestrates Aspergillus fumigatus-Induced Eosinophil Activation Independently of Canonical Toll-Like Receptor (TLR)/C-Type-Lectin Receptor (CLR) Signaling - Dietschmann, Axel; Schrüfer, Sebastian; Westermann, Stefanie; Henkel, Fiona; Castiglione, Kirstin; Willebrand, Ralf; Adam, Jasmin; Ruland, Jurgen; Lang, Roland; Sheppard, Donald C.; Esser-Von-Bieren, Julia; Radtke, Daniel; et al. (Mbio, 2022)
Eosinophilia is associated with various persisting inflammatory diseases and often coincides with chronic fungal infections or fungal allergy as in the case of allergic bronchopulmonary aspergillosis (ABPA). Here, we show that intranasal administration of live Aspergillus fumigatus conidia causes fatal lung damage in eosinophilic interleukin-5 (IL-5)-transgenic mice. To further investigate the activation of eosinophils by A. fumigatus, we established a coculture system of mouse bone marrow-derived eosinophils (BMDE) with different A. fumigatus morphotypes and analyzed the secretion of cytokines, chemokines, and eicosanoids. A. fumigatus-stimulated BMDE upregulated expression of CD11b and downregulated CD62L and CCR3. They further secreted several proinflammatory mediators, including IL-4, IL-13, IL-18, macrophage inflammatory protein-1 alpha (MIP-1 alpha)/CC chemokine ligand 3 (CCL3), MIP-1 beta/CCL4, and thromboxane. This effect required direct interaction and adherence between eosinophils and A. fumigatus, as A. fumigatus culture supernatants or A. fumigatus mutant strains with impaired adhesion elicited a rather poor eosinophil response. Unexpectedly, canonical Toll-like receptor (TLR) or C-type-lectin receptor (CLR) signaling was largely dispensable, as the absence of MYD88, TRIF, or caspase recruitment domain-containing protein 9 (CARD9) resulted in only minor alterations. However, transcriptome analysis indicated a role for the PI3K-AKT-mTOR pathway in A. fumigatus-induced eosinophil activation. Correspondingly, we could show that phosphatidylinositol 3-kinase (PI3K) inhibitors successfully prevent A. fumigatus-induced eosinophil activation. The PI3K pathway in eosinophils may therefore serve as a potential drug target to interfere with undesired eosinophil activation in fungus-elicited eosinophilic disorders. IMPORTANCE Allergic bronchopulmonary aspergillosis (ABPA) is caused by the fungus Aspergillus fumigatus, afflicts about five million patients globally, and is still a noncurable disease. ABPA is associated with pronounced lung eosinophilia. Activated eosinophils enhance the inflammatory response not only by degranulation of toxic proteins but also by secretion of small effector molecules. Receptors and signaling pathways involved in activation of eosinophils by A. fumigatus are currently unknown. Here, we show that A. fumigatus-elicited activation of eosinophils requires direct cell-cell contact and results in modulation of cell surface markers and rapid secretion of cytokines, chemokines, and lipid mediators. Unexpectedly, this activation occurred independently of canonical Toll-like receptor or C-type lectin receptor signaling. However, transcriptome analysis indicated a role for the PI3K-AKT-mTOR pathway, and PI3K inhibitors successfully prevented A. fumigatus-induced eosinophil activation. The PI3K pathway may therefore serve as a potential drug target to interfere with undesired eosinophil activation in fungus-elicited eosinophilic disorders.
CRIS-Team WoS Importer:2022-06-24

PI3K signaling orchestrates eosinophil activation against Aspergillus fumigatus independently of canonical TLR/CLR signaling - Dietschmann, Axel; Schrüfer, Sebastian; Westermann, Stefanie; Henkel, F.; Castiglione, Kathrin; Willebrand, Ralf; Ruland, J.; Lang, Roland; Esser-Von-Bieren, J.; Radtke, Daniel; Krappmann, Sven; Vöhringer, David (MYCOSES, 2021)
CRIS-Team WoS Importer:2021-10-08

Proteome Analysis Reveals the Conidial Surface Protein CcpA Essential for Virulence of the Pathogenic Fungus Aspergillus fumigatus - Voltersen, Vera; Blango, Matthew G.; Herrmann, Sahra; Schmidt, Franziska; Heinekamp, Thorsten; Strassburger, Maria; Krueger, Thomas; Bacher, Petra; Lother, Jasmin; Weiss, Esther; Huenniger, Kerstin; Liu, Hong; et al. (Mbio, 2018)
Aspergillus fumigatus is a common airborne fungal pathogen of humans and a significant source of mortality in immunocompromised individuals. Here, we provide the most extensive cell wall proteome profiling to date of A. fumigatus resting conidia, the fungal morphotype pertinent to first contact with the host. Using liquid chromatography-tandem mass spectrometry (LC-MS/MS), we identified proteins within the conidial cell wall by hydrogen-fluoride (HF)-pyridine extraction and proteins exposed on the surface using a trypsin-shaving approach. One protein, designated conidial cell wall protein A (CcpA), was identified by both methods and was found to be nearly as abundant as hydrophobic rodlet layer-forming protein RodA. CcpA, an amphiphilic protein, like RodA, peaks in expression during sporulation on resting conidia. Despite high cell wall abundance, the cell surface structure of ΔccpA resting conidia appeared normal. However, trypsin shaving of ΔccpA conidia revealed novel surface-exposed proteins not detected on conidia of the wild-type strain. Interestingly, the presence of swollen ΔccpA conidia led to higher activation of neutrophils and dendritic cells than was seen with wild-type conidia and caused significantly less damage to epithelial cells in vitro In addition, virulence was highly attenuated when cortisone-treated, immunosuppressed mice were infected with ΔccpA conidia. CcpA-specific memory T cell responses were detectable in healthy human donors naturally exposed to A. fumigatus conidia, suggesting a role for CcpA as a structural protein impacting conidial immunogenicity rather than possessing a protein-intrinsic immunosuppressive effect. Together, these data suggest that CcpA serves as a conidial stealth protein by altering the conidial surface structure to minimize innate immune recognition.IMPORTANCE The mammalian immune system relies on recognition of pathogen surface antigens for targeting and clearance. In the absence of immune evasion strategies, pathogen clearance is rapid. In the case of Aspergillus fumigatus, the successful fungus must avoid phagocytosis in the lung to establish invasive infection. In healthy individuals, fungal spores are cleared by immune cells; however, in immunocompromised patients, clearance mechanisms are impaired. Here, using proteome analyses, we identified CcpA as an important fungal spore protein involved in pathogenesis. A. fumigatus lacking CcpA was more susceptible to immune recognition and prompt eradication and, consequently, exhibited drastically attenuated virulence. In infection studies, CcpA was required for virulence in infected immunocompromised mice, suggesting that it could be used as a possible immunotherapeutic or diagnostic target in the future. In summary, our report adds a protein to the list of those known to be critical to the complex fungal spore surface environment and, more importantly, identifies a protein important for conidial immunogenicity during infection.
EVALuna2:36419

Pseudomonas aeruginosa-Derived Volatile Sulfur Compounds Promote Distal Aspergillus fumigatus Growth and a Synergistic Pathogen-Pathogen Interaction That Increases Pathogenicity in Co-infection - Scott, Jennifer; Sueiro-Olivares, Monica; Ahmed, Wadar; Heddergott, Christoph; Zhao, Can; Thomas, Riba; Bromley, Michael; Latge, Jean-Paul; Krappmann, Sven; Fowler, Stephen; Bignell, Elaine; Amich, Jorge (Frontiers in Microbiology, 2019)
Pathogen-pathogen interactions in polymicrobial infections are known to directly impact, often to worsen, disease outcomes. For example, co-infection with Pseudomonas aeruginosa and Aspergillus fumigatus, respectively the most common bacterial and fungal pathogens isolated from cystic fibrosis (CF) airways, leads to a worsened prognosis. Recent studies of in vitro microbial cross-talk demonstrated that P. aeruginosa-derived volatile sulfur compounds (VSCs) can promote A. fumigatus growth in vitro. However, the mechanistic basis of such cross-talk and its physiological relevance during co-infection remains unknown. In this study we combine genetic approaches and GC-MS-mediated volatile analysis to show that A. fumigatus assimilates VSCs via cysteine (CysB)- or homocysteine (CysD)-synthase. This process is essential for utilization of VSCs as sulfur sources, since P. aeruginosa-derived VSCs trigger growth of A. fumigatus wild-type, but not of a 1cysB1cysD mutant, on sulfur-limiting media. P. aeruginosa produces VSCs when infecting Galleria mellonella and co-infection with A. fumigatus in this model results in a synergistic increase in mortality and of fungal and bacterial burdens. Interestingly, the increment in mortality is much greater with the A. fumigatus wild-type than with the 1cysB1cysD mutant. Therefore, A. fumigatus' ability to assimilate P. aeruginosa derived VSCs significantly triggers a synergistic association that increases the pathobiology of infection. Finally, we show that P. aeruginosa can promote fungal growth when growing on substrates that resemble the lung environment, which suggests that this volatile based synergism is likely to occur during co-infection of the human respiratory airways.
CRIS-Team WoS Importer:2019-11-01

RNAseq analysis of Aspergillus fumigatus in blood reveals a just wait and see resting stage behavior - Irmer, Henriette; Tarazona, Sonia; Sasse, Christoph; Olbermann, Patrick; Loeffler, Jurgen; Krappmann, Sven; Conesa, Ana; Braus, Gerhard H. (BMC Genomics, 2015)
Invasive aspergillosis is started after germination of Aspergillus fumigatus conidia that are inhaled by susceptible individuals. Fungal hyphae can grow in the lung through the epithelial tissue and disseminate hematogenously to invade into other organs. Low fungaemia indicates that fungal elements do not reside in the bloodstream for long.We analyzed whether blood represents a hostile environment to which the physiology of A. fumigatus has to adapt. An in vitro model of A. fumigatus infection was established by incubating mycelium in blood. Our model allowed to discern the changes of the gene expression profile of A. fumigatus at various stages of the infection. The majority of described virulence factors that are connected to pulmonary infections appeared not to be activated during the blood phase. Three active processes were identified that presumably help the fungus to survive the blood environment in an advanced phase of the infection: iron homeostasis, secondary metabolism, and the formation of detoxifying enzymes.We propose that A. fumigatus is hardly able to propagate in blood. After an early stage of sensing the environment, virtually all uptake mechanisms and energy-consuming metabolic pathways are shut-down. The fungus appears to adapt by trans-differentiation into a resting mycelial stage. This might reflect the harsh conditions in blood where A. fumigatus cannot take up sufficient nutrients to establish self-defense mechanisms combined with significant growth.
EVALuna2:7692

Signaling events driving Aspergillus fumigatus-induced eosinophil activation - Adam, Jasmin; Graf, Lisa-Marie; Westermann, Stefanie; Vöhringer, David; Krappmann, Sven (International Journal of Medical Microbiology, 2025)
Allergic bronchopulmonary aspergillosis is an incurable disease caused by the environmental mold Aspergillus fumigatus. This hypersensitivity pneumonia is characterized by an inflammatory type 2 immune response, accompanied by influx of eosinophils into the lung. To investigate the mode of action of eosinophils and the signaling events triggered by A. fumigatus, we used an in vitro coculture system of murine bone marrow-derived eosinophils confronted with conidia. Using small-molecule inhibitors, we identified signaling modules of eosinophils in the course of A. fumigatus confrontation. Eosinophils reduced fungal metabolic activity, but inhibition of relevant signaling modules did not affect this phenomenon upon eosinophil confrontation. A. fumigatus-induced secretion of Th2 cytokines and chemokines by eosinophils engaged proto-oncogene tyrosine-protein kinase Src, phosphatidylinositol 3-kinase, p38 mitogen-activated protein kinase as well as calcium cations and to some extent serine/threonine-protein kinase Akt and protein arginine deiminase 4. Src and PI3K kinases were also involved in A. fumigatus-mediated ROS production and regulation of eosinophils surface receptors. Especially Src and PI3K inhibitors prevented A. fumigatus-induced eosinophil activation. Taken together, identification of signaling cascades of eosinophils during their interaction with A. fumigatus provides relevant insights into the host-pathogen interaction in the context of ABPA to yield therapeutic perspectives.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Allergic bronchopulmonary aspergillosis; Allergic lung inflammation; Granulocytes; PI3K; Src

Tet-on, or Tet-off, that is the question: Advanced conditional gene expression in Aspergillus - Wanka, Franziska; Cairns, Timothy; Boecker, Simon; Berens, Christian; Happel, Anna; Zheng, Xiaomei; Sun, Jibin; Krappmann, Sven; Meyer, Vera (Fungal Genetics and Biology, 2015)
In Aspergillus, controlled gene expression is often achieved using the reverse tetracycline-controlled transactivator (rtTA) dependent Tet-on system, whereby transcription is activated in a titratable manner by addition of the tetracycline derivative doxycycline. The complementary Tet-off system utilises the tetracycline-controlled transactivator (tTA) component to quantitatively reduce gene expression. In this study, we utilised a synthetic biological approach to engineer highly optimised Tet-off conditional expression systems in Aspergillus niger and Aspergillus fumigatus. Steps for delivery of these tools include utilising codon optimised cassette components, testing several promoters for improved genetic stability and validating two modified luciferase reporters for highly accurate measurements of gene expression. The Tet-off cassettes developed in this study enable facile and quantitative functional analysis, as validated by Tet-off analysis of genes involved in chitin synthesis and cell wall polarity in A. niger, and para-aminobenzoic acid synthesis in A. fumigatus. We also used a racA(G18V) dominant allele to demonstrate that Tet-off in A. niger enables gene over-expression and downregulation in a single isolate. Additionally, we used the improved luciferase reporters to show that the Tet-off cassette in A. niger enables quantification of gene oscillations. In order to demonstrate that synthetic biological approaches developed here are broadly applicable to engineering transcriptional circuits in filamentous fungi, we used our strategy for improving cassette stability by promoter replacement in the A. niger Tet-on system, which resulted in a modified Tet-on cassette with higher stability in recipient genomes.
EVALuna2:7694

Th2 cells promote eosinophil-independent pathology in a murine model of allergic bronchopulmonary aspergillosis - Dietschmann, Axel; Schruefer, Sebastian; Krappmann, Sven; Vöhringer, David (European Journal of Immunology, 2020)
Repeated inhalation of airborne conidia derived from the fungus Aspergillus fumigatus (Af) can lead to a severe eosinophil-dominated inflammatory condition of the lung termed allergic bronchopulmonary aspergillosis (ABPA). ABPA affects about 5 million individuals worldwide and the mechanisms regulating lung pathology in ABPA are poorly understood. Here, we used a mouse model of ABPA to investigate the role of eosinophils and T cell-derived IL-4/IL-13 for induction of allergic lung inflammation. Selective deletion of IL-4/IL-13 in T cells blunted the Af-induced lung eosinophilia and further resulted in lower expression of STAT6-regulated chemokines and effector proteins such as Arginase 1, Relm-α, Relm-β, and Muc5a/c. Eosinophil-deficient ΔdblGata mice showed lower IL-4 expression in the lung and the number of Th2 cells in the lung parenchyma was reduced. However, expression of the goblet cell markers Clca1 and Muc5a/c, abundance of mucin-positive cells, as well as weight gain of lungs were comparable between Af-challenged ΔdblGata and WT mice. Based on these results, we conclude that T cell-derived IL-4/IL-13 is essential for Af-induced lung eosinophilia and inflammation while eosinophils may play a more subtle immunomodulatory role and should not simply be regarded as pro-inflammatory effector cells in ABPA.
CRIS-Team Scopus Importer:2020-03-20
Keywords: allergy; Aspergillus fumigatus; eosinophils; IL-4/IL-13; lung inflammation

The Essential Thioredoxin Reductase of the Human Pathogenic Mold Aspergillus fumigatus Is a Promising Antifungal Target - Binder, Jasmin; Shadkchan, Yana; Osherov, Nir; Krappmann, Sven (Frontiers in Microbiology, 2020)
The identification of cellular targets for antifungal compounds is a cornerstone for the development of novel antimycotics, for which a significant need exists due to increasing numbers of susceptible patients, emerging pathogens, and evolving resistance. For the human pathogenic mold Aspergillus fumigatus, the causative agent of the opportunistic disease aspergillosis, only a limited number of established targets and corresponding drugs are available. Among several targets that were postulated from a variety of experimental approaches, the conserved thioredoxin reductase (TrxR) activity encoded by the trxR gene was assessed in this study. Its essentiality could be confirmed following a conditional TetOFF promoter replacement strategy. Relevance of the trxR gene product for oxidative stress resistance was revealed and, most importantly, its requirement for full virulence of A. fumigatus in two different models of infection resembling invasive aspergillosis. Our findings complement the idea of targeting the reductase component of the fungal thioredoxin system for antifungal therapy.
CRIS-Team Scopus Importer:2020-07-24
Keywords: aspergillosis; conditional promoter replacement; essentiality; TetOFF; thioredoxin

The infectious propagules of Aspergillus fumigatus are coated with antimicrobial peptides - Dümig, Michaela; Binder, Jasmin; Gaculenko, Anastasia; Daul, Franziska; Winandy, Lex; Hasenberg, Mike; Gunzer, Matthias; Fischer, Reinhard; Künzler, Markus; Krappmann, Sven (Cellular Microbiology, 2021)
Fungal spores are unique cells that mediate dispersal and survival in the environment. For pathogenic fungi encountering a susceptible host, these specialised structures may serve as infectious particles. The main causative agent of the opportunistic disease aspergillosis, Aspergillus fumigatus, produces asexual spores, the conidia, that become dissipated by air flows or water currents but also serve as propagules to infect a susceptible host. We demonstrate that the defX gene of this mould encodes putative antimicrobial peptides resembling cysteine-stabilised (CS)αβ defensins that are expressed in a specific spatial and temporal manner in the course of asexual spore formation. Localisation studies on strains expressing a fluorescent proxy or tagged defX alleles expose that these antimicrobial peptides are secreted to coat the conidial surface. Deletion mutants reveal that the spore-associated defX gene products delay the growth of Gram-positive Staphylococcus aureus and demonstrate that the defX gene and presumably its encoded spore-associated defensins confer a growth advantage to the fungal opponent over bacterial competitors. These findings have implications with respect to the ecological niche of A. fumigatus that serves as a ‘virulence school’ for this human pathogenic mould; further relevance is given for the infectious process resulting in aspergillosis, considering competition with the host microbiome or co-infecting microorganisms to break colonisation resistance at host surfaces.
CRIS-Team Scopus Importer:2021-03-12
Keywords: aspergillosis; defensin-like peptide; fungal virulence

The master regulator MAT1-1-1 of fungal mating binds to its targets via a conserved motif in the human pathogen Aspergillus fumigatus - Ramsak, Barbara; Markau, Jessica; Pazen, Tobias; Dahlmann, Tim A.; Krappmann, Sven; Kück, Ulrich (G3 : Genes, Genomes, Genetics, 2021)
Mating-type transcription factors are master regulators of sexually related signal transduction pathways in fungi; however, their recognition of specific DNA sequences from target genes is widely undetermined. Here, we identified and characterized the DNA-binding sequence of the MAT1-1-1 alpha-box domain transcription factor from the human pathogen Aspergillus fumigatus. In order to explore MAT1-1-1 DNA-binding targets, we used the previously reported MAT1-1-1 binding motif from Penicillium chrysogenum, in a bioinformatics approach. We identified 18 A. fumigatus genes carrying the MAT1.1 sequence in their upstream region, among them genes for the a-pheromone precursor (PpgA), G-protein-coupled pheromone receptor (PreA), and for TomA, an unidentified protein. To validate our prediction further, quantification of transcript levels showed a decrease in expression of ppgA, tomA, and others in a MAT1-1 deletion strain. For a functional analysis of the binding sites, truncated variants of the A. fumigatus MAT1-1-1 gene were introduced into Escherichia coli for heterologous expression. The yield of recombinant protein was further optimized for the AfMAT1-1-178–235 variant that harbors an extended alpha-box domain. AfMAT1-1-178–235 bound to a subset of the most strongly upregulated genes: ppgA, preA, and tomA. The DNA-binding specificity was confirmed by testing mutated binding sequences, as well as performing competition experiments with specific and non-specific sequences. Finally, equilibrium dissociation constants of 1.83 6 0.1 and 1.45 6 0.26 mM were determined for AfMAT1-1-178–235 and fusion protein GST-AfMAT1-1-178–235. Collectively, these findings provide further insights into AfMAT1-1-1-mediated gene expression and imply that alpha-box domain regulators from other members of Eurotiales control fungal development in a conserved manner.
CRIS-Team Scopus Importer:2021-03-26
Keywords: DNA-binding motif; Escherichia coli protein synthesis; Human pathogen Aspergillus fumigatus; Mating type; Transcription factor

The novel Aspergillus fumigatus MAT1-2-4 mating-type gene is required for mating and cleistothecia formation - Yu, Yidong; Amich, Jorge; Will, Christine; Eagle, Carly E.; Dyer, Paul S.; Krappmann, Sven (Fungal Genetics and Biology, 2017)
Sexual propagation accompanied by recombination and the formation of spore-containing fruiting bodies is a cornerstone of fungal genetics and biology. In the human pathogen Aspergillus fumigatus sexual identity has previously been shown to be determined by MAT1-1-1 or MAT1-2-1 genes which act as transcriptional regulators and are present within idiomorphs found at the MAT locus. We here report the identification and first characterization of a further novel gene, termed MAT1-2-4, that is present in the MAT1-2 idiomorph of A. fumigatus. A mating-type swapping strategy was used to achieve an unbiased deletion of the MAT1-2-4 gene with no impact on MAT1-2-1 gene expression. Phenotypical characterization of the resulting strain revealed an inability to mate with the compatible MAT1-1 progenitor, demonstrating that the MAT1-2-4 gene product is a genuine mating-type factor required for correct sexual development. A GPI-anchored protein of unknown function was identified as interaction partner. However, no functional role in the mating process or ascosporogenesis could be demonstrated by deletion analysis for this latter protein, although a role in heterokaryon formation is suggested. Bioinformatic analysis also demonstrated the presence of MAT1-2-4 homologues in some, but not all, other Aspergillus species and the evolutionary origins and implications of the MAT1-2-4 gene are discussed.
EVALuna2:7737

The opportunistic pathogen Aspergillus fumigatus coats its infectious propagules with antimicrobial peptides - Duemig, Michaela; Binder, Johannes; Gaculenko, Anastasia; Daul, F.; Hasenberg, M.; Gunzer, M.; Krappmann, Sven (2018)
EVALuna2:213342

Three-dimensional light sheet fluorescence microscopy of lungs to dissect local host immune-aspergillus fumigatus interactions - Amich, Jorge; Mokhtari, Zeinab; Strobel, Marlene; Vialetto, Elena; Sheta, Dalia; Yu, Yidong; Hartweg, Julia; Kalleda, Natarajaswamy; Jarick, Katja J.; Brede, Christian; Jordán-Garrote, Ana Laura; Thusek, Sina; et al. (Mbio, 2020)
Aspergillus fumigatus is an opportunistic fungal pathogen that can cause life-threatening invasive lung infections in immunodeficient patients. The cellular and molecular processes of infection during onset, establishment, and progression of A. fumigatus infections are highly complex and depend on both fungal attributes and the immune status of the host. Therefore, preclinical animal models are of paramount importance to investigate and gain better insight into the infection process. Yet, despite their extensive use, commonly employed murine models of invasive pulmonary aspergillosis are not well understood due to analytical limitations. Here, we present quantitative light sheet fluorescence microscopy (LSFM) to describe fungal growth and the local immune response in whole lungs at cellular resolution within its anatomical context. We analyzed three very common murine models of pulmonary aspergillosis based on immunosuppression with corticosteroids, chemotherapy-induced leukopenia, or myeloablative irradiation. LSFM uncovered distinct architectures of fungal growth and degrees of tissue invasion in each model. Furthermore, LSFM revealed the spatial distribution, interaction, and activation of two key immune cell populations in antifungal defense: alveolar macrophages and polymorphonuclear neutrophils. Interestingly, the patterns of fungal growth correlated with the detected effects of the immunosuppressive regimens on the local immune cell populations. Moreover, LSFM demonstrates that the commonly used in-tranasal route of spore administration did not result in complete intra-alveolar deposition, as about 80% of fungal growth occurred outside the alveolar space. Hence, characterization by LSFM is more rigorous than by previously used methods employing murine models of invasive pulmonary aspergillosis and pinpoints their strengths and limitations. IMPORTANCE The use of animal models of infection is essential to advance our understanding of the complex host-pathogen interactions that take place during Aspergillus fumigatus lung infections. As in the case of humans, mice need to suffer an immune imbalance in order to become susceptible to invasive pulmonary aspergillosis (IPA), the most serious infection caused by A. fumigatus. There are several immunosuppressive regimens that are routinely used to investigate fungal growth and/or immune responses in murine models of invasive pulmonary aspergillosis. However, the precise consequences of the use of each immunosuppressive model for the local immune populations and for fungal growth are not completely understood. Here, to pin down the scenarios involving commonly used IPA models, we employed light sheet fluorescence microscopy (LSFM) to analyze whole lungs at cellular resolution. Our results will be valuable to optimize and refine animal models to maximize their use in future research.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Aspergillus fumigatus; Host immune response; Host-pathogen interactions; In vivo fungal growth; Invasive aspergillosis; Light sheet fluorescence microscopy; Lung immunity; Lung infection; Microscopy/imaging; Murine models of invasive pulmonary aspergillosis; Whole-organ imaging

TomA, the target of MAT1-1 in Aspergillus fumigatus, is required for cleistothecia formation presumably in a mating-type-specific manner - Pazen, Tobias; Ramsak, B.; Kueck, U.; Krappmann, Sven (MYCOSES, 2022)
Mating-type transcription factors are master regulators of sexually related signal transduction pathways in fungi; however, their recognition of specific DNA sequences from target genes is widely undetermined. Here, we identified and characterized the DNA-binding sequence of the MAT1-1-1 alpha-box domain transcription factor from the human pathogen Aspergillus fumigatus. In order to explore MAT1-1-1 DNA-binding targets, we used the previously reported MAT1-1-1 binding motif from Penicillium chrysogenum, in a bioinformatics approach. We identified 18 A. fumigatus genes carrying the MAT1.1 sequence in their upstream region, among them genes for the α-pheromone precursor (PpgA), G-protein-coupled pheromone receptor (PreA), and for TomA, an unidentified protein. To validate our prediction further, quantification of transcript levels showed a decrease in expression of ppgA, tomA, and others in a MAT1-1 deletion strain. For a functional analysis of the binding sites, truncated variants of the A. fumigatus MAT1-1-1 gene were introduced into Escherichia coli for heterologous expression. The yield of recombinant protein was further optimized for the AfMAT1-1-178–235 variant that harbors an extended alpha-box domain. AfMAT1-1-178–235 bound to a subset of the most strongly upregulated genes: ppgA, preA, and tomA. The DNA-binding specificity was confirmed by testing mutated binding sequences, as well as performing competition experiments with specific and non-specific sequences. Finally, equilibrium dissociation constants of 1.83 ± 0.1 and 1.45 ± 0.26 µM were determined for AfMAT1-1-178–235 and fusion protein GST-AfMAT1-1-178–235. Collectively, these findings provide further insights into AfMAT1-1-1-mediated gene expression and imply that alpha-box domain regulators from other members of Eurotiales control fungal development in a conserved manner.<br
CRIS-Team WoS Importer:2022-09-23

Transcriptional response of Aspergillus fumigatus to copper and the role of the Cu chaperones - Anabosi, Duaa; Meir, Zohar; Shadkchan, Yana; Handelman, Mariana; Abou-Kandil, Ammar; Yap, Annie; Urlings, Daniel; Gold, Morgan S.; Krappmann, Sven; Haas, Hubertus; Osherov, Nir (Virulence, 2021)
Aspergillus fumigatus is the leading cause of life-threatening invasive mold infections in immunocompromised individuals. This ubiquitous saprophyte possesses several natural attributes allowing it to evade the immune system, including the ability to withstand high toxic Cu concentrations within the phagosomes of macrophages and neutrophils. We previously established that at high levels, Cu binds and activates the A. fumigatus transcription factor AceA, which upregulates the expression of the Cu exporter CrpA to expel excess Cu. Deletion of aceA or crpA result in extreme Cu sensitivity and attenuated virulence. To identify other elements participating in resistance to Cu, we performed a genome-wide analysis of the transcriptome by RNAseq to analyze the AceA-dependent response of A. fumigatus to excess Cu. We deleted key genes whose transcription was strongly upregulated by high Cu, including those encoding homologs of the three Cu chaperones cox17, atx1 and ccs1. Detailed analysis of these genes indicates that in A. fumigatus, cox17 is an essential gene with a possible role in respiration, the atxA gene product participates in reductive iron uptake and ccsA encodes the Cu chaperone activating A. fumigatus Sod1. Interestingly, although the ccsA-null strain was extremely sensitive to high Cu and oxidative stress, it was not attenuated in virulence in a mouse model of invasive pulmonary aspergillosis. Our work provides (i) a detailed view of the genome-wide transcriptional response of A. fumigatus to excess Cu, (ii) identification of the AceA-dependent transcriptome and (iii) analysis of the roles of the three Cu chaperones cox17, atxA and ccsA.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Aspergillus fumigatus; Cu chaperones; Cu transcriptome; oxidative stress; virulence

When green and red mycology meet: Impressions from an interdisciplinary forum on virulence mechanisms of phyto- and human-pathogenic fungi - Yu, Yidong; Hube, Bernhard; Kämper, Jörg; Meyer, Vera; Krappmann, Sven (Virulence, 2017)
Fungal infections pose a constant threat to plants and humans, but detailed knowledge about pathogenesis, immunity, or virulence is rather scarce. Due to the fact that a certain overlap in the armoury of infection exists between plant- and human-pathogenic fungi, an interdisciplinary forum was held in October 2016 at the Institute for Clinical Microbiology, Immunology and Hygiene in Erlangen under the organisational umbrella from two special interest groups of German microbial societies. Scientific exchange and intense discussion of this timely topic was fostered by bringing together renowned experts in their respective fields to present their thoughts and recent findings in the course of a plenary lecture and six themed sessions, accompanied by oral and poster contributions of young researchers. By targeting the topic of fungal virulence mechanisms from various angles and in the context of plant and human hosts, some common grounds and exciting perspectives could be deduced during this vibrant scientific event.
EVALuna2:7738